Implementasi Program Literasi Untuk Meningkatkan Kecerdasan Lingusitik Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Siti Holilah; Dede Rubai Misbahul Alam (Turabian: Jurnal Pendidikan Islam, 2023)
The literacy program at SDN Tambun 04 is a program that aims to familiarize students with reading 15 minutes before learning begins, to improve their linguistic intelligence. Islamic Religious Education lessons are one of the lessons that are integrated with this literacy program. In this research, the writer uses descriptive qualitative research, with the method of observation, interviews and documentation from resource persons, which will be used as data in the preparation of this thesis. The resource persons in this study included the principal of SDN Tambun 04, the teacher council, committee and parents of students as well as the fifth grade students of SDN Tambun 04. The results of the research that the authors get lead to several conclusions, namely: 1) the 15-minute reading habituation program before learning begins can improve students' linguistic intelligence, as evidenced by the ability of students to present their reading results in the development stage either orally or in writing. 2) PAI Learning Implementation Plan incorporates literacy programs into subjects